Analisis Penggunaan Media Sosial Instagram Dalam Membangun Brand Awareness UMKM Bandeng Presto Prisha - Susanty, Rina; Restaty, Santa Margaretha Niken; Pujiastuti, Yanti Lestari (Universitas Mercu Buana, 2024)
This study aims to examine how the MSME Bandeng Presto Prisha utilizes Instagram to build brand awareness. Using a qualitative descriptive method with a case study approach, data were obtained through in-depth interviews, observations, and documentation. The results show that Instagram significantly supports branding processes through product visualisation, customer testimonials, and brand positioning. Content strategies remain basic and inconsistent, yet they manage to reach the targeted market active on social media. This study contributes to the development of digital marketing strategies for culinary-based MSMEs.